MODERN GROWTH OF DEVELOPMENT OF INNOVATIVE ACTIVITIES, HEALTHCARE SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Kurbanov Ikhtiyor Khikmatovich (Western European Studies, 2025)
The transition to an innovative path of development of the Republic of Uzbekistan involves a significant change in the role and importance of innovation and its result - innovation. Innovations are being introduced into all spheres of life from production and management to consumption and the social sphere, the most important of which is healthcare. Health is also an important factor in wealth and economic activity, as it is related to age, lifestyle, social status, learning, and the spread of social connections and interpersonal support. The health care system is the most important area of society. Health care management in Uzbekistan is traditionally based on administrative methods, and investment in the health care system is based on resource provision indicators (beds, number of employees, etc.).
Keywords: Innovative path; activity; mesolevel